Recent progress in photochemical radical di- and mono-fluoromethylation. Issue 22 (14th May 2019) - Koike, Takashi; Akita, Munetaka
Abstract : Di- and mono-fluoromethyl radicals can be easily accessed by photochemical protocols. Abstract : Recently, photoinduced radical difluoromethylation has emerged as a step-economical synthetic method of CHF2 -containing compounds. In this article, difluoromethylation of alkenes, isonitriles and aryl bromides promoted by photoredox catalysis is described together with a non-catalytic photoinduced system. Representative reactions will be discussed for each highlighted difluoromethylating reagent. In addition, related monofluoromethylation with their corresponding monofluoromethylating reagents is also discussed.